Upaya Pelestarian Kesenian Kuda Renggong Desa Cikurubuk Sumedang Jawa Barat Melalui Pengembangan Hand Drawing - Ali, Ferdiansyah; Dewanto, Yahya; Darmawan, Aditya; Budiman (Magenta | Official Journal STMK Trisakti, 2024)
The art of Kuda Renggong is an art originating from the village of Cikurubuk Sumedang, West Java which features one to four horses following the rhythm of music, over time the art of renggong horses is lost to time because the people of Cikurubuk village prefer to imitate outside culture, only a handful of people who understand the art of performing renggong horses and even many are still wrong in interpreting it, especially from children and adolescents. The methodology used in this research is descriptive qualitative using the ADDIE model approach (Analysis, Design, Development, Implementation, Evaluation). The purpose of this design is an effort to introduce the art of renggong horses suitable for reintroducing this almost forgotten art in order to re-educate the people of cikurubuk village and the public to continue to preserve the art of renggong horses with hand drawing animation media with the concept of drawing my life as an attractive and varied information media using audio visuals made storytelling. The results of this study indicate that the development of hand drawings has proven effective in efforts to preserve the art of Kuda Renggong in Cikurubuk Village, Sumedang Regency. The utilization of hand drawings can increase the understanding and appreciation of the community, especially the younger generation, of the cultural values contained in Kuda Renggong. Abstrak Kesenian Kuda Renggong adalah seni yang berasal dari Desa Cikurubuk Sumedang, Jawa Barat yang menampilkan satu sampai empat ekor kuda mengikuti irama musik, seiring berjalannya waktu kesenian kuda renggong hilang termakan zaman karena orang-orang desa cikurubuk lebih suka meniru budaya luar, hanya segelintir orang yang mengerti akan seni pertunjukan kuda renggong bahkan masih banyak yang salah dalam mengartikannya terlebih dari anak-anak dan remaja. Metodologi yang digunakan penelitian ini adalah kualitatif deskriptif dengan menggunakan pendekatan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Tujuan perancangan ini adalah upaya pengenalan kesenian kuda renggong cocok untuk mengenalkan kembali kesenian yang hampir terlupakan ini guna mengedukasi kembali masyarakat desa cikurubuk dan umum untuk terus melestarikan kesenian kuda renggong dengan media animasi hand drawing berkonsep draw my life sebagai media informasi secara menarik dan variatif dengan menggunakan audio visual yang dibuat bercerita. Hasil penelitian ini menunjukkan bahwa pengembangan hand drawing terbukti efektif dalam upaya pelestarian kesenian Kuda Renggong di Desa Cikurubuk, Kabupaten Sumedang. Pemanfaatan hand drawing dapat meningkatkan pemahaman dan apresiasi masyarakat, khususnya generasi muda, terhadap nilai-nilai budaya yang terkandung dalam Kuda Renggong.